The Demise of Rural Life in Graham Swift’s Wish You Were Here - Kucała, Bożena (American & British Studies Annual, 2012)
This article argues that Graham Swift’s recent novel Wish You Were Here, which depicts the erosion of rural life in contemporary England, may be treated as a post-rural novel; it both overtly alludes to the tradition of rural fiction and the pastoral convention in literature as well as suggests that the lifestyle that sustained this type of literature is currently disintegrating. Although focused on the limited experience of a particular family, the novel forges connections between a series of recent personal disasters and national and international events whose impact may be felt even in rural Devon. The narrative is overshadowed by the protagonist’s traumatic memories, and above all by his current mission to bury his brother, a soldier killed in Iraq. The burial that ends the story is a bitterly ironic return to the family farm, which, however, will never again serve the function for which it was once built.